2019
DOI: 10.2174/1871520619666190930130732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Somatostatin and Vitamin C on the Fatty Acid Profile of Breast Cancer Cell Membranes

Abstract: Background: Vitamin C (Vit C) is an important physiological antioxidant with growing applications in cancer. Somatostatin (SST) is a natural peptide with growth inhibitory effect in several mammary cancer models. Objective: The combined effects of SST and Vit C supplementation have never been studied in breast cancer cells so far. Methods: We used MCF-7 and MDA-MB231 breast cancer cells incubated with SST for 24h, in the absence and presence of Vit C, at their EC50 concentrations, to evaluate membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Another study that used a combination of vitamin C with somatostatin on MCF-7 and MDA-MB231 breast cancer cells caused membrane remodeling in MCF-7 cells that could affect signaling processes. In MCF-7 cells the combination of vitamin C and somatostatin significantly decreased EGFR (Epidermal Growth Factor Receptors) and MAPK (Mitogen-Activated Protein Kinase) signaling compared to MDA-MB231 cells (Hanikoglu et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Another study that used a combination of vitamin C with somatostatin on MCF-7 and MDA-MB231 breast cancer cells caused membrane remodeling in MCF-7 cells that could affect signaling processes. In MCF-7 cells the combination of vitamin C and somatostatin significantly decreased EGFR (Epidermal Growth Factor Receptors) and MAPK (Mitogen-Activated Protein Kinase) signaling compared to MDA-MB231 cells (Hanikoglu et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…It was reported that this cytotoxic effect is related to the pro-oxidant properties of vitamin C, which can activate the transcription factor NF-kappa B and inhibit cell growth. In addition, by producing hydrogen peroxide and activating hydroxyl radicals, vitamin C can reduce cell replication mechanisms and cancer cell viability by inducing DNA strand damage, controlling mitotic activity, and damaging mitochondria and cell membranes (Lee, 2009;Gonzales et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations